E2F7 promotes mammalian target of rapamycin inhibitor resistance in hepatocellular carcinoma after liver transplantation. Issue 10 (1st July 2022) - Ling, Sunbin; Zhan, Qifan; Jiang, Guangjiang; Shan, Qiaonan; Yin, Lu; Wang, Rui; Que, Qingyang; Wei, Xuyong; Xu, Shengjun; Yu, Jiongjie; Zhou, Wei; Zhang, Lincheng; et al.
Abstract : The mammalian target of rapamycin (mTOR) pathway is frequently deregulated and has critical roles in cancer progression. mTOR inhibitor has been widely used in several kinds of cancers and is strongly recommended in patients with hepatocellular carcinoma (HCC) after liver transplantation (LT). However, the poor response to mTOR inhibitors due to resistance remains a challenge. Hypoxia‐associated resistance limits the therapeutic efficacy of targeted drugs. The present study established models of HCC clinical samples and cell lines resistance to mTOR inhibitor sirolimus and screened out E2F7 as a candidate gene induced by hypoxia and promoting sirolimus resistance. E2F7 suppressed mTOR complex 1 via directly binding to the promoter of the TSC1 gene and stabilizes hypoxia‐inducible factor‐1α activating its downstream genes, which are responsible for E2F7‐dependent mTOR inhibitor resistance. Clinically, low E2F7 expression could be an effective biomarker for recommending patients with HCC for anti‐mTOR–based therapies after LT. Targeting E2F7 synergistically inhibited HCC growth with sirolimus in vivo. E2F7 is a promising target to reverse mTOR inhibition resistance. Collectively, our study points to a role for E2F7 in promoting mTOR inhibitor resistance in HCC and emphasizes its potential clinical significance in patients with HCC after LT. Abstract : Experiments using human hepatocellular carcinoma patient samples and cell lines identify E2F7 as a candidate hypoxia‐induced gene that promotes resistance to mammalian target of rapamycin inhibitors.